Synthesis and in vitro Evaluation of 2-heteroarylidene-1-tetralone Derivatives as Monoamine Oxidase Inhibitors - Amakali, Klaudia T.; Legoabe, Lesetja J.; Petzer, Anél; Petzer, Jacobus P. (Drug Research, 2018)
The present study investigates the human monoamine oxidase (MAO) inhibition properties of a series of twelve 2-heteroarylidene-1-tetralone derivatives. Also included are related cyclohexylmethylidene, cyclopentylmethylidene and benzylidene substituted 1-tetralones. These compounds are related to the 2-benzylidene-1-indanone class of compounds which has previously been shown to inhibit the MAOs, with specificity for the MAO-B isoform. The target compounds were synthesised by the Claisen-Schmidt condensation between 7-methoxy-1-tetralone or 1-tetralone, and various aldehydes, under acid (hydrochloric acid) or base (potassium hydroxide) catalysis. The results of the MAO inhibition studies showed that the 2-heteroarylidene-1-tetralone and related derivatives are in most instances more selective inhibitors of the MAO-B isoform compared to MAO-A. (2E)-2-Benzylidene-7-methoxy-3,4-dihydronaphthalen-1(2 H)-one (IC50=0.707 μM) was found to be the most potent MAO-B inhibitor, while the most potent MAO-A inhibitor was (2E)-2-[(2-chloropyridin-3-yl)methylidene]-7-methoxy-3,4-dihydronaphthalen-1(2 H)-one (IC50=1.37 μM). The effect of the heteroaromatic substituent on MAO-B inhibition activity, in decreasing order was found to be: cyclohexyl, phenyl>thiophene>pyridine, furane, pyrrole, cyclopentyl. This study concludes that, although some 2-heteroarylidene-1-tetralone derivatives are good potency MAO inhibitors, in general their inhibition potencies, particularly for MAO-B, are lower than structurally related chalcones and 1-indanone derivatives that were previously studied.
Keywords: monoamine oxidase; inhibition; Parkinson’s disease; Alzheimer’s disease; heteroarylidene-1-tetralone; 2-benzylidene-1-tetralone